PEMBELAJARAN SEJARAH BERWAWASAN LINGKUNGAN - Ahmad, Tsabit Azinar (Indonesian Journal of Conservation, 2013)
This paper analyzes the relevance of history education and environmental issues. Based on literature study, there are relevance between history and environmental issues. Since 1970s, new study in history has developed namely environmental history. The emergence of environmental history became starting point of Environmental History Learning (EHL). EHL emphasized the importance of the progress of mutual relations between man and nature. EHL implementation can be done with chronological-integrative models, selected themes, and thematic-chronological model. The improvements for aspect of Ã¢â¬Åcontent and contextÃ¢â¬Â are needed to achieve effective learning outcomes. Aspect of content has subject matter essence and developing for historiography of environmental history.ÃÂ  Then aspects of context include teachers, atmosphere, and a learning system that emphasizes the real problem. EHL has role as a roadmap of the various environmental issues that are currently happening. In addition, EHL also provide role models and best practices in order to process planning and handling environmental problems do not return the same stumbling dilemma. Development of environmental history learning is expected to internalize awareness and preservation of the environment. Keywords: teaching history, environmental history, environmental education. ÃÂ Tulisan ini mengaji relevansi pendidikan sejarah dan masalah-masalah lingkungan. Dari kajian literatur, terdapat keterkaitan antara sejarah dan masalah-masalah lingkungan. Sejak tahun 1970an telah berkembang kajian baru dalam sejarah yang disebut sejarah lingkungan. Berkembangnya sejarah lingkungan menjadi titik tolak berkembangnya Pembelajaran Sejarah Berwawasan Lingkungan (PSBL). PSBL menekankan arti penting perkembangan hubungan timbal balik antara manusia dan alam. Penerapan PSBL dapat dilakukan dengan model kronologis-integratif, kapita selekta, dan tematis-kronologis. Untuk mewujudkan capaian yang efektif, perlu pembenahan dalam aspek content dan context. Aspek content meliputi esensi materi dan perkembangan historiografi sejarah lingkungan. Kemudian aspek context meliputi guru, suasana, dan sistem pembelajaran yang menekankan pada masalah nyata. PSBL berperan sebagai roadmap dari beragam isu lingkungan yang saat ini terjadi. Selain itu, PSBL juga berperan dalam memberikan role models dan best practices agar proses perencanaan dan penangan masalah lingkungan tidak kembali terantuk masalah yang sama.ÃÂ  ÃÂ Pengembangan pembelajaran berwawasan lingkungan diharapkan mampu menanamkan nilai kepedulian dan pelestarian terhadap lingkungan Kata kunci: pembelajaran sejarah, sejarah lingkungan, pendidikan lingkungan. ÃÂ